P611 High seroprevalence of mycoplasma genitalium in the general adult population of germany. (14th July 2019) - Reichert, Felix; Waterboer, Tim; Poethko-Müller, Christina; Jansen, Klaus
Abstract : Background: Mycoplasma genitalium (MG) is one of the most common bacterial sexually transmitted infections (STI). Nevertheless, knowledge about the immune response is scarce and seroprevalence has only been assessed in selected populations. In HIV-negative blood donors seroprevalence was 5.5%, in patients with pelvic inflammatory disease 17%. We estimated MG seroprevalence in the general adult population in Germany. Methods: We retrospectively analysed sera of the population-based German National Health Interview and Examination Survey 1998 for MG antibodies using a pre-validated, multiplex, fluorescent bead-based assay. To avoid cross-reactivity, two unconserved regions of adhesion proteins, MgPaN and rMgPa were chosen as antigens. The thresholds for seropositivity were set at 1000 median fluorescence intensity units by visual inspection of inflection points. Overall seropositivity for MG was defined as concomitant seropositivity for both antigens. To assure representativeness, survey weights were applied for calculation of prevalence and 95% confidence intervals(CI). Design-based F was computed as test of independence. Results: Sera of 6038 participants were analysed. Participants were aged 17–79 years (y) (median 44y), 51% were female. Overall weighted seroprevalence was 6.5% (95%CI: 5.7–7.3%), and by age-group 17–19y 0.3% (0.1–1.5%), 20–24y 1.9% (0.9–3.8%), 25–29y 6.7% (4.6–9.8%), 30–39y 9.1% (7.4–11.1%), 40–49y 10.8% (8.9–13.0%), 50–59y 4.5% (3.4–5.9%), 60–69y 3.3% (2.2–5.1%), and 70–79y 4.6% (2.9–7.4%). In the age-group 20–29y, women had a higher seroprevalence (7.5%, 95%CI: 5.0–11.1%) than men (2.1%, 95%CI: 1.1–4.0%; p=0.001). Conclusion: Compared to other studies, our results for MG seroprevalence in the general adult population in Germany are plausible. The earlier increase in women is similar to the pattern in other STI such as Chlamydia trachomatis infection. Seroprevalence dropped in participants aged 50 or more but remained stable at a low level until old age, indicating long antibody persistence or continuous sexual interactions in parts of the population. However, longitudinal studies are necessary to clarify immunological processes. Disclosure: No significant relationships.